A STEAM Approach based on Balinese Local Wisdom to Students' Reading and Writing Literacy - Luh Gede Rossy Popsiani; Putu Aditya Antara; Gusti Ayu Putu Sukma Trisna (Universitas Pendidikan Ganesha, 2025)
Students' suboptimal performance, minimal student involvement in understanding the reading content and in rewriting information coherently, and a lack of innovation in learning approaches that integrate local cultural potential. This study aims to analyze the STEAM approach based on Balinese local wisdom on the literacy of second-grade elementary school students. The study used a Quasi-Experimental design with a nonequivalent control group posttest-only design. The population consisted of 204 second-grade students from 7 schools. The sample was obtained through random sampling, with the class unit as the intact group: 16 students in the experimental group and 17 in the control group. Data were collected through a 16-item essay test. The results of the t-test in SPSS showed significant differences in students' literacy before and after the implementation of the STEAM approach based on Balinese local wisdom. Thus, the STEAM approach, based on Balinese local wisdom, has a significant effect in improving the literacy of second-grade elementary school students. This study implies that this approach can be an effective, context-specific learning strategy for improving the literacy quality of elementary school students.